The Business Process for Receipt and Disbursement of Cash Through Website: Case Study of Riverstone Hotel & Cottage - Syaputri, Diva Wahyu; Riwajanti, Nur Indah; Sumiadji, Sumiadji (East Asian Journal of Multidisciplinary Research, 2024)
This study aims to present an effective business process model to tackle issues related to the cash inflow and outflow cycle at Riverstone Hotel & Cottage. It utilizes Research and Development (R&D) as the research type and follows the ADDIE method, consisting of three stages: analysis, design, and development. The findings suggest the necessity of a website system featuring separate cash inflow and outflow menus for the administrative and front office departments, as well as for the hotel's services (rooms and halls) and expenditures. Implementing real-time management can help reduce processing delays during the calculation and input of room/hall prices across different platforms. Moreover, daily/monthly transaction reports can be conveniently accessed from the provided menu options, eliminating the need for manual recalculations.